Electricity Trade and Economic Growth in South Africa - Hlongwane, Nyiko Worship; Daw, Olebogeng David (International Journal of Energy Economics and Policy, 2023)
The study investigates the relationship between electricity trade and economic growth in South Africa. The study utilised time series data spanning from 1985 to 2022 collected from secondary sources like the Quantec. The study employed DF-GLS and KPSS unit root, ARDL Bounds cointegration test, ARDL ECM model, Granger causality and residual diagnostics tests. The study discovered the presence of short and long run negative relationships between electricity trade and economic growth in South Africa. The Granger causality revealed unidirectional causality running from economic growth to electricity generation in South Africa. The study recommends the reduction of electricity trade to boost economic growth in South Africa for the period understudy. The study further makes the following recommendations, in future the studies should consider investigating electricity infrastructure and economic growth in South Africa utilising either time series or panel data analysis.